Mecanismos adrenérgicos do núcleo parabraquial lateral e da área Kölliker Fuse/A7 no controle da ingestão de água e sódio - Gasparini, Silvia (Universidade Federal de São Carlos, 2009)
The blockade of serotonergic receptors with methysergide or the activation of α2-adrenoceptors with moxonidine into the lateral parabrachial nucleus (LPBN) increases water and 0.3 M NaCl intake in rats treated with furosemide (FURO) combined with captopril (CAP). Besides LPBN, also the Kölliker-Fuse nucleus/A7 area (KF/A7 area) located at the rostral and lateral end of the LPBN is important for water intake. In the present study we investigated the effects of bilateral injections of noradrenaline (the endogenous neurotransmitter for α-adrenoceptors) alone or combined with the α2-adrenoceptor antagonist RX 821002 into the KF/A7 area or into LPBN. The effects of moxonidine, methysergide or proglumide on FURO + CAPinduced water and 0.3 M NaCl intake were also investigated. In addition, we tested simultaneously water and sodium intake and renal excretion in rats treated with FURO + CAP that received noradrenaline into the KF/A7 area to investigate the effects of this treatment on water and sodium balance. The effects of noradrenaline into KF/A7 area in rats treated with FURO + CAP on cardiovascular responses were also investigated. Male Holtzman rats with bilateral stainless steel guide-cannulas implanted into KF/A7 area or LPBN were used. FURO + CAP-induced 0.3 M NaCl intake strongly increased after bilateral injections of noradrenaline (80 or 160 nmol) into LPBN (26.5 ± 5.9 and 20.7 ± 2.0 ml/2 h, vs. salina: 4.4 ± 0.9 ml/2 h) or into the KF/A7 area (31.5 ± 6.1 and 25.9 ± 4.7 ml/2 h, vs. salina: 7.2 ± 1.6 ml/2 h). However, increases in water intake caused by noradrenaline injected in KFA7 area are not consistent. Bilateral injections of RX 821002 into LPBN or KF/A7 area abolished the effects of noradrenaline in the same areas on 0.3 M NaCl intake (7.5 ± 2.5 and 9.8 ± 4.4 ml/2 h, respectively). Moxonidine (0.5 nmol) injected bilaterally into the KF/A7 area increased 0.3 M NaCl intake (39.5 ± 6.3 ml/3 h v.s. vehicle: 5.7 ± 1.5 ml/3 h) and water intake (26.8 ± 4.2 ml/3 h v.s. vehicle: 11.6 ± 1.3 ml/3 h), while methysergide (4 μg) or proglumide (50 μg) into the KF/A7 area did not alter 0.3 M NaCl or water intake. Injections of noradrenaline (80 or 160 nmol/0.2 μl) into the KF/A7 did not alter urinary volume, potassium excretion or sodium excretion. However, noradrenaline into the KF/A7 induced a positive cumulative sodium balance (5179 ± 1045 μEq/3 h v.s saline: 2 ± 545 μEq/3 h) and a cumulative water balance (25.2 ± 4.5 ml/3 h v.s. saline: 2.5 ± 4.1 ml/3 h). In rats with a polyethylene tubing (PE-10 connected to a PE-50) inserted into abdominal aorta through femoral artery, injections of noradrenaline (80 or 160 nmol/0.2 μl) into KF/A7 area promoted a powerful increased in blood pressure (69 ± 12 and 61 ± 10 mmHg, respectively). The results of the present study suggest that α2-adrenoceptor activation is a common mechanism in the KF/A7 area and LPBN to facilitate sodium intake. In addition, injections of noradrenaline into the KF/A7 area induce renal responses to reduce sodium excretion. However, the serotonergic or cholecystokinergic mechanisms that control sodium intake are present in LPBN, not in the KF/A7 area.
Keywords: Fisiologia; Núcleo parabraquial lateral; Ingestão de água e sódio; Excreção renal; CIENCIAS BIOLOGICAS::FISIOLOGIA